Effectiveness of Pay for Performance Incentive System on Projects Performance - Ni Wayan Kurnia Dewi; I Made Dwi Jendra Sulastra; I Made Agus Putrayasa (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study examines the effectiveness of implementing a project performance-based employee incentive system at a state-owned construction company in Indonesia, PT PP (Persero) Tbk. The data were analyzed using a quantitative approach, with the Key Performance Indicator (KPI) for each project before and after the implementation of the project performance-based incentive system. The data was tested using the Wilcoxon test to see if there were statistical differences in project performance before and after the implementation of the project performance-based employee incentive system. The results show that there are statistically significant differences in project KPIs before and after the implementation of the project performance-based employee incentive system. The project KPIs show a higher average value than before the implementation of this system. This research contributes especially for construction companies regarding the pros and cons of implementing a project performance-based incentive system because it is proven to be effective in motivating employees in increasing the average performance of their projects which affect the company's overall performance.